A Measuring Satisfaction of Member UPN Veteran Yogyakarta Cooperative Whatsapp Group: Webqual 4.0 Model Adoption - Sriyono, Sriyono; Simanjuntak, Oliver Samuel; Agusdin, Riza Prapascatama; Tahalea, Sylvert Prian (RSF Conference Series: Engineering and Technology, 2022)
This research adopted WebQual 4.0 to determine user satisfaction from members of the UPN "Veteran" Yogyakarta Whatsapp Group (WAG) cooperative. A total of 150 samples were obtained to be ready for analysis. Correlation and Regression Analysis were used to analyze. The analysis results show that the WAG members of the UPN "Veteran" Yogyakarta Cooperative are not satisfied with the quality of the information provided so far and the use of WAG as a medium for disseminating information. However, they are satisfied with the interactions carried out by the WAG admin in the group. In the future, it is hoped that the Yogyakarta "Veteran" UPN Cooperative can improve the way they provide information and pay attention to the quality of information before it is distributed to their WAG.